2021
DOI: 10.1002/bmb.21562
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of virtual laboratory simulations before, during, and postCOVID‐19 recovery phase: An Animal Biotechnology case study

Abstract: This study presents an evaluation of integrating virtual laboratory simulations in assessment design of a biotechnology course at Taylor's University in Malaysia before, during and post‐COVID recovery phases. The purpose was to investigate how virtual laboratory simulations were integrated as part of the assessments of a practical‐embedded course—the aim being to evaluate students' acceptance and perception of using virtual simulation. A total of 46 students, across three different study cohorts (August 2019, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Despite their good scores in the assessment, nearly all students think that the practical part of the course must be conducted in a real environment; they want to contact their instructor and deal with real equipment. A similar opinion was noted in a Malaysian study in which virtual simulations were introduced as part of the Biotechnology undergraduate course, though their perception of the use of these tools was good 14 . The authors referred it to the circumstances accompanying the lockdown as it was associated with overwhelming feelings of fear and anxiety, in addition, those students had limited online resources at their homes 14 .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Despite their good scores in the assessment, nearly all students think that the practical part of the course must be conducted in a real environment; they want to contact their instructor and deal with real equipment. A similar opinion was noted in a Malaysian study in which virtual simulations were introduced as part of the Biotechnology undergraduate course, though their perception of the use of these tools was good 14 . The authors referred it to the circumstances accompanying the lockdown as it was associated with overwhelming feelings of fear and anxiety, in addition, those students had limited online resources at their homes 14 .…”
Section: Discussionmentioning
confidence: 74%
“…14 The authors referred it to the circumstances accompanying the lockdown as it was associated with overwhelming feelings of fear and anxiety, in addition, those students had limited online resources at their homes. 14 Furthermore, other studies on online learning of Medical Anatomy confirmed that students prefer practicing in traditional labs, as this allows them to interact with their peers and the instructors, ask questions and discuss vague points. 15,16 An additional reason might explain the Egyptian students' opinion, as we must emphasize that the environment in the high school educational system does not expose students to E-learning.…”
Section: Questionnaire Itemsmentioning
confidence: 99%
“…As shown in Figure 3, ILW can train cognitive, psychomotor, and affective domain skills. Training in the three domains in the chemistry curriculum is essential, especially in higher education 49–51 . In addition, laboratory work is part of training students' ability to organize and develop them and not to be afraid of failure 52,53 …”
Section: Resultsmentioning
confidence: 99%
“…The use of computer simulations can enhance traditional instructions, especially the laboratory activities [1]. LVOS continued to play an important role in courses with laboratory classes owing to intermittent lockdowns and evolving infectious strains that will deter full access to IPL classes [2]. Virtual Lab Simulations can contribute to the increased study activity and motivation.…”
Section: Introductionmentioning
confidence: 99%